PERAN HUMAS DALAM PENINGKATAN PENERIMAAN MAHASISWA BARU DI UNIVERSITAS SLAMET RIYADI SURAKARTA - Dian Esti Nurati, Budi Setyawan, Maya Sekar Wangi & (Transformasi, 2016)
The development of communication with overtime into various fields more specific. One of theseareas is a field public relations ( PR) or usual also called public relations. Public relations orPR is an institution to establish and maintaining good relations with public internal , andexternal. Background research is the role of public relations on the popularity and positiveimage Slamet Riyadi Surakarta University , against the increase freshmen public relations ofSlamet Riyadi University Surakarta considering how specialized in acceptance of new students.This research in a qualitative.Data collected through interviews with informants, literaturestudy, and analysis documents. Research results on the role of public relations in the increasefreshmen the public relations: role in terms of planning program , planning strategy , thestrategy , and evaluation. With suggestions of this research is the need for public relationsslamet riyadi university improving communication effective as well as management and publicrelations strategy in the university slamet riyadi to get more capable of increasing popularityand image slamet riyadi university that can improve the acceptance of new studentsKey words: planning message , communicating message , the role of public relations